The fire / 3. - Patterson, James, 1947- (Witch & wizard, 2011)
Whisty Allgood and her brother Whit must come up with a better plan after her efforts to use her fight and fire to defeat The One Who is the One--the evil leader who killed their family and banned everything they hold dear in the world--only adds to his power.